Effect of growth age on the polyphenol content of materials from Tithonia diversifolia (Hemsl.) - Scull, Idania; Savón, Lourdes; Ruíz, T. E.; Herrera, Magaly (Cuban Journal of Agricultural Science, 2022)
The effect of growth age (30, 60 and 90 days) on the polyphenol content of Tithonia diversifolia (Hemsl.) materials collected in eastern Cuba was evaluated. A completely random design with 10 repetitions was applied. Total polyphenols and total condensed tannins were determined in seven tithonia materials (2, 3, 12, 14, 17, 23 and 24) in the rainy and dry seasons. An analysis of variance was performed, according to a completely random design in a 3 x 7 factorial arrangement. The factors were the growth age (30, 60 and 90 days) and the T. diversifolia materials (2, 3, 12, 14, 17, 23 and 24). There was an increase in phenolic compounds with growing age and the highest values were reached at 90 days. Material 3 showed the highest content of total polyphenols (4.62 % DM) in the dry season, and 12 reached the highest concentration of total condensed tannins (2.33 % DM) in the rainy season. The studied materials showed differences in the content and type of phenolic compounds in both seasons of the year. This experiment will help to select the materials with the greatest biological potential for animal feeding. Future researches are suggested to identify the biological activity of these substances and their relation with the beneficial effects in animals. Key words: secondary metabolites, tannins, buttercup, phytochemical composition